Disability and disadvantage: selection, onset, and duration effects - Stephen P. Jenkins; John A. Rigg (University of Essex, Institute for Social and Economic Research (ISER), 2003)
This paper analyses the economic disadvantage experienced by disabled persons of working-age using data from the British Household Panel Survey. We argue that there are three sources of disadvantage among disabled persons: pre-existing disadvantage among those who become disabled (a selection effect), the effect of disability onset itself, and the effects associated with remaining disabled post-onset. We show that employment rates fall with disability onset, and continue to fall the longer a disability spell lasts, whereas average income falls sharply with onset but then recovers subsequently (though not to pre-onset levels).
Keywords: 330